Incidence and risk factors of delirium in multi-center Thai surgical intensive care units: A prospective cohort study - Tanyong Pipanmekaporn (2018)
© 2015 Pipanmekaporn et al. Background: Delirium in intensive care units increases morbidity and mortality risk. The incidence and risk factors of delirium among studies. This study therefore aimed to determine the incidence and risk factors of delirium in Thai university-based surgical intensive care units. Methods: A multi-center, prospective cohort study was conducted. All patients who had been admitted to surgical intensive care units (SICU) between April 2011 and January 2012 were enrolled. Delirium was diagnosed using the Intensive Care Delirium Screening Checklists (ICDSC). The univariable and multivariable risk regression analyses were analyzed and presented as risk ratio (RR) and 95 % confidence interval (CI). Results: The overall incidence of delirium was 3.6 % (162 of 4450, 95 % CI 3.09-4.19 %) whilst the incidences of delirium for patients being admitted ≤48 and >48 h were 0.7 % (21 of 2967, 95 % CI 0.41-1.01 %) and 8.3 % (141 of 1685, 95 % CI 7.04-9.68 %), respectively. The incidence of delirium on each study site was significantly different (range between 0 and 13.9 %, P < 0.001). Delirious patients had a significantly higher age (65.3 ± 15.6 versus 61.8 ± 17.3 years, P = 0.013), higher Acute Physiology and Chronic Health Evaluation II score (APACHE II score) (16 (12-23) versus 10 (7-15), P < 0.001), and higher sequential organ failure assessment score (5 (2-8) versus 2 (1-5), P < 0.001). The median duration of delirium was 3 (1-5) days. Delirious patients had significantly longer duration of ICU stay (8 (5-19) versus 2 (1-4), P < 0.001) and higher ICU mortality rate (23.5 versus 8.1 %, P < 0.001). Sepsis (RR = 3.70, 95 % CI 2.33-5.90, P < 0.001), exposure to sedative medications (RR = 3.54, 95 % CI 2.13-5.87, P < 0.001), higher APACHE II score (RR = 2.79, 95 % CI 1.98-3.95, P < 0.001), thoracic surgery (RR = 1.74, 95 % CI 1.09-2.78, P = 0.021), and emergency surgery (RR = 1.70, 95 % CI 1.09-2.65, P = 0.019) were independent risk factors of delirium in SICU. Conclusions: Sepsis, exposure to sedative medications, higher APACHE II score, thoracic surgery, and emergency surgery were independent risk factors of delirium in Thai university-based surgical intensive care units.